The factors that contribute claims towards motor insurance / Nor Syakilla Mat Isa - Mat Isa, Nor Syakilla (Faculty of Business and Management, 2010)
The subject matter of this project paper is on the “Factors that contribute Claims towards Motor Insurance. The issues of claims towards motor insurance had been investigated over the time. As a result, it show that road accident is one of the major causes of the death and injuries in Malaysia. Besides that, the road accident also has a relationship with motor insurance claims which is growing of total road accident will be increasing the claim on the motor insurance.The research is conducted to study the level of claims and the factors that contribute the claim towards motor insurance. The factors that contribute and effect claims can be measure through some criteria such as vehicle design, speed of operation, road design and driver behavior.The result from the finding indicates that most of respondents have been involved in road accident and also make claims due to the accident. Furthermore, the result of the research also show that the major factors that contribute claims towards motor insurance is speed of the vehicle which the most important factor that lead to the road accident. As a conclusion, the result of this study to provide information for Insurance Association regarding the factors which increase the claims on motor insurance and for underwriter to build coverage on the policy for the Insured according to the problem occurs.